Perancangan UI/UX Sistem Informasi Penilaian Kinerja Guru Berbasis Web di SMPN Satap Pekuwolan - Agus Salim; Nurul Huda (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
Teacher performance evaluation is a crucial component in improving the quality of education. However, the manual evaluation process at SMPN Satap Pekuwolan presents several challenges, such as delays in data compilation, lack of transparency, and limited access to information. This study aims to design the user interface (UI) and user experience (UX) of a web-based information system for teacher performance evaluation to support a more efficient, transparent, and structured process.The research employed a User-Centered Design (UCD) methodology, consisting of four main stages: understanding the usage context, specifying user requirements, designing solutions, and evaluating the design. Data collection was carried out through direct observation, interviews with school stakeholders, and questionnaires distributed to potential users, including teachers and the principal. The interface prototype was developed using Figma, and evaluated through usability testing with five participants to gather feedback on ease of use and user satisfaction.The results showed that the developed UI/UX design met most of the user needs, with an average System Usability Scale (SUS) score of 82, categorized as “good.” Features such as digital assessment forms, performance history, and data visualization dashboards effectively improved the efficiency and accessibility of the evaluation process.